Catur Piwulang of Sunan Drajat: The Humanitarian Turn in the History of Islamic Da'wah in Java and its Relevance to Islamic Education - Nur Laili; Lala Afrizia; Nur Saidah; Irfan Afandi (Universitas Islam Negeri Sumatera Utara, 2026)
This study is motivated by the importance of re-examining the da'wah strategies of the Walisongo, which contributed significantly to the Islamization of Java through peaceful, adaptive, and human-centered approaches. One of the most prominent figures in this regard was Sunan Drajat, whose teachings of Catur Piwulang emphasized social concern and the dignity of human beings. This study aims to analyze Catur Piwulang as a form of humanistic da'wah in the history of Islamization in Java and to examine its relevance to Islamic education. This research employed a descriptive qualitative approach using library research and a historical-hermeneutic perspective. Data were collected from books, scholarly articles, and historical sources related to Sunan Drajat’s da'wah, Islamic humanism, and Islamic education, and were analyzed through content analysis and historical analysis. The findings reveal that Catur Piwulang—which teaches giving a cane to the blind, food to the hungry, clothing to the naked, and shelter to those exposed to rain—represents a da'wah strategy oriented toward fulfilling basic human needs, upholding human dignity, and strengthening social solidarity. These values reflect the principles of Islamic humanism and correspond with the humanistic theories of Paulo Freire and Abraham Maslow. Furthermore, Catur Piwulang demonstrates strong relevance to Islamic education by promoting empathy, social responsibility, justice, and humanitarian awareness. In conclusion, Sunan Drajat’s Catur Piwulang can be understood as a form of humanistic da'wah that remains relevant as a paradigm for developing moderate, inclusive, and socially civilized Islamic da'wah and education.